MENINGKATKAN KINERJA KEUANGAN : EVALUASI MANAJEMEN PIUTANG DI PT. ADI SARANA ARMADA Tbk - Edy Sarwono; Sukamto, Sukamto; Rimi Gusliana Mais (Juremi: Jurnal Riset Ekonomi, 2024)
The aim of this research is to determine and assess the performance of the company PT. Adi Sarana Armada Tbk in implementing its receivables management policy, whether it is effective or ineffective. The research method used is a quantitative method with data analysis methods using descriptive methods. This research uses secondary data sources originating from company financial reports for the 2021-2023 period. The problem formulation in this research is about the management of receivables at PT. Adi Sarana Armada Tbk is it effective. Based on the research results, it can be concluded that receivables management at PT. Adi Sarana Armada Tbk for the 2021-2023 period has been managed quite well. The average receivables in the research period showed a decline from year to year which could benefit the company because more funds were turned into cash than remained in receivables. The distribution turnover shows a value above the standard figure, so it can be said that the company has an efficient and clear distribution turnover, has quite good distribution quality and collection success. The company is in good condition, because the capital contained in the utility can be converted quickly into cash